Does death make us all equal? Conformism and status-seeking under mortality salience - Raimondello Orsini; Elisa Ciaramelli; Caterina Giannetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
The thought of one's own death induces anxiety and threatens self-esteem. According to Terror Management Theory, to reduce this existential threat individuals typically embrace their cultural worldview, and seek for an increase in self-esteem and status by improving their productivity. Within an experimental economy setting, this paper investigates the effect of Mortality Salience (MS) on individual productivity, using for the first time a real-effort task where the economic incentive is to not perform. We investigated whether the improvement in productivity was significantly driven by self-esteem or status seeking, providing either private feedback alone or, additionally, public feedback. Always controlling for participants' individual susceptibility to the MS induction, our results indicate that subjects generally tend to be more sensitive to in-group conformity under MS compared to a control (Music) induction condition. That is, they initially improve their performance to enhance self-esteem, but then homologate to average performance levels, consistent with the incentive not to perform. However, for a subset of less materialistic participants, with strong susceptibility to MS, performance levels constantly improved along the task.
Keywords: C91; C92; D12; 330